NEGATIVE VESSEL REMODELING IN STARGARDT DISEASE QUANTIFIED WITH VOLUME-RENDERED OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY. Issue 9 (September 2021) - Reich, Michael; Dreesbach, Michelle; Boehringer, Daniel; Schottenhamml, Julia; Gehring, Esteban; Scholl, Hendrik P. N.; Inglin, Nadja; Agostini, Hansjuergen; Reinhard, Thomas; Lagrèze, Wolf A.; Spaide, Richard F.; Lange, Clemens; et al.
Abstract : Purpose: To quantify retinal vasculature changes in Stargardt disease1 (STGD1) with volume-rendered optical coherence tomography angiography. Methods: Optical coherence tomography angiography volumes from healthy subjects and two subgroups of patients with STGD1 with the presence/absence of definitely decreased autofluorescence areas were compared. Optical coherence tomography angiography vessel surface area and vessel volume were measured in central zones (Z) of 1-, 2-, and 3-mm diameter. Results: Twenty nine eyes of 15 patients with STGD1 (20/9 eyes with/without definitely decreased autofluorescence) and 30 eyes of 15 controls contributed data. An enlarged foveal avascular zone was found in patients with STGD1 without and even more with definitely decreased autofluorescence associated with a vessel rarefication in central and also paracentral zones with unnoticeable autofluorescence. Vessel surface area and vessel volume were reduced in both STGD1 subgroups for all zones ( P < 0.0001). Stargardt disease 1 eyes when compared to without definitely decreased autofluorescence showed reduced vessel surface area and vessel volume in Z2+3 (both P < 0.05). Conclusion: Volume rendering of optical coherence tomography angiography in STGD1 shows a reduced retinal flow in the central macula. This is most likely secondary to loss of neurosensory tissue with disease progression and therefore not likely be favorably influenced by gene transfer and retinal pigment epithelial transplantation. Retinal blood flow assessed by 3D volume-rendered optical coherence tomography angiography could serve as surrogate marker for vascular changes of the central retina. Abstract : Supplemental Digital Content is Available in the Text.Volume rendering of optical coherence tomography angiography in Stargardt disease 1 shows a reduced retinal vascular flow in the central macula and may serve a surrogate marker for vascular changes of the central retina to be considered in treatment trials.